Authorities Of The Constitutional Court In Dissoluting Political Parties - Yulianto, Winasis; Silvana Amalia, Dyah (International Journal of Educational Research & Social Sciences, 2023)
Article 24C paragraph (1) of the 1945 Constitution of the Republic of Indonesia, hereinafter referred to as the 1945 Constitution of the Republic of Indonesia states that, the Constitutional Court has the authority to try at the first and final levels whose decision is final to review laws against the Constitution, decide on disputes over the authority of state institutions whose powers are granted by the Constitution, decide on the dissolution of political parties, and decide on disputes about the results of general elections. The dissolution of political parties through this legal aspect is the result of the third amendment to the 1945 Constitution of the Republic of Indonesia. Previously, the dissolution of political parties was carried out by the government. The dissolution of political parties through legal channels is a consequence of the statement that Indonesia is a state of law. This is also due to the provisions of Article 1 paragraph (2) of the 1945 Constitution of the Republic of Indonesia which states that Sovereignty is in the hands of the people and implemented according to the Constitution. The provisions of Article 1 paragraph (2) of the 1945 Constitution of the Republic of Indonesia constitute a shift from the supremacy of the People's Consultative Assembly to the supremacy of the Constitution The research method used in this study is a normative juridical research method, which means that this research uses legal norms as a means to analyze problems. While the approach method in this study uses: statute approach, conceptual approach, historical approach, and comparison approach. To analyze in this research is to use the interpretation of legal systematics.The conclusion will answer the problems raised in this study.